Epidemic investigation of the jaundice outbreak in Girdharnagar, Ahmedabad, Gujarat, India, 2008 - Chauhan Naresh; Prajapati Prakash; Trivedi Atul; Bhagyalaxmi A (Wolters Kluwer Medknow Publications, 2010)
Background: Since 1976, seven outbreaks of hepatitis E occurred in Ahmedabad. Clusters of jaundice cases were reported on June 19, 2008, by a civic center, Girdharnagar ward, Ahmedabad. Objectives: The objectives were as follows: (1) to identify the etiological agent, source of outbreak, and mode of transmission; (2) to propose a control measure based on the outbreak investigation. Materials and Methods: We defined a case as an acute illness with (a) a discrete onset of symptoms and (b) jaundice or elevated serum aminotransferase levels, from March to September 2008 in the households of the Girdharnagar ward. We collected data through a door-to-door survey and hospital records. We described the outbreak in terms of time, place, and person. We collected laboratory investigation reports of case patients admitted to the civil hospital. To test our hypothesis we conducted a retrospective cohort study to find out the relative risk for hepatitis. We conducted environment investigation to find out the source of contamination of water supply. Results: A total 233 case patients of hepatitis were identified with the attack rate of 10.9/1000 population. Cases were reported in all the age groups with a higher attack rate in the age group of 20-29 years (18.5/1000). Out of 17 case patients, 16 were positive for the hepatitis E IgM antibody. The attack rate was two times more among those who were exposed to the leaking pipeline than the non-exposed (RR=2.3, 95% CI 1.76, 2.98). Environmental investigation also confirmed the sewage contamination of drinking water in the distribution system. Conclusion: The outbreak was due to hepatitis E virus. We recommended a temporary alternative water supply, repair of the leakages, and water quality surveillance.